Spatial Distribution And Synoptic Conditions Of Snow Accumulation And Snow Ablation In The West Siberian Plain - Bednorz, Ewa; Wibig, Joanna (Quaestiones Geographicae, 2015)
The mean duration of snow coverage in the West Siberian Plain is approximately eight months in the north to about five months in the south. While the period of intense snow melting is short (one or two months between March and May), snow accumulation persists for most of the cold season. Snow accumulation is associated with negative anomalies of sea level pressure, which means increased cyclonal activity and weaker than normal Siberian High. Much lower anomalies of sea level pressure occur during snow ablation. This suggests smaller influence of air circulation on snow cover reduction in spring.